A LABORATORY SCALE INVESTIGATION OF MANNING ROUGHNESS COEFFICIENT IN OPEN CHANNEL BED WITH DIFFERENT GRAIN SIZE AND SLOPES - Yılmaz, Damla; Aras, Egemen; Vaheddoost, Babak (My University, 2023)
Efforts for getting the maximum efficiency from the existing water resources and to implement new projects are getting more attention these days. Determining the flow resistance for the project design and control process in open channels requires sophisticated applications. It is usually essential to be aware of the characteristics of the channel and flow to determine the hydraulic roughness, which represents the resistance of the flow. Hence, empirical calculation and evaluation of the hydraulic roughness will support future design and planning processes. In this study, four different particle sizes (d50= 28mm, 17.5mm, 4mm, and 1.75mm) that were fixed on blocks were used. These particle sizes were then used as the bed covering together with, three different horizontal bed slopes, and flow rates in the experiments to determine the associated Manning roughness, n. During the experiment, Froude number values were examined and it was determined that, in 32 experiments the flow regime can be considered as subcritical. Alternatively, the Lotter method was used to confirm the roughness values obtained by the Manning equation. It was concluded that the roughness values obtained by the selected methods have good concordance with each other.
Keywords: Roughness coefficient; Open channel flows; Manning; Grain diameter